Nanoscale visualization of hot carrier generation and transfer at non-noble metal and oxide interface - Singh, Ranveer; Sial, Qadeer Akbar; Han, Seung ik; Nah, Sanghee; Park, Ji Yong; Seo, Hyungtak (Journal of Materials Science and Technology, 2022)
The conversion efficiency of energy-harvesting devices can be increased by utilizing hot-carriers (HCs). However, due to ultrafast carrier-carrier scattering and the lack of carrier injection dynamics, HC-based devices have low efficiencies. In the present work, we report the effective utilization of HCs at the nanoscale and their transfer dynamics from a non-noble metal to a metal oxide interface by means of real-space photocurrent mapping by using local probe techniques and conducting femtosecond transient absorption (TA) measurements. The photocurrent maps obtained under white light unambiguously show that the HCs are injected into the metal oxide layer from the TiN layer, as also confirmed by conductive atomic force microscopy. In addition, the increased photocurrent in the bilayer structure indicates the injection of HCs from both layers due to the broadband absorption efficiency of TiN layer, passivation of the surface states by the top TiN layer, and smaller barrier height of the interfaces. Furthermore, electrostatic force microscopy and Kelvin probe force microscopy provide direct evidence of charge injection from TiN to the MoOx film at the nanoscale. The TA absorption spectra show a strong photo-bleaching signal over wide spectral range and ultrafast decaying behavior at the picosecond time scale, which indicate efficient electron transfer from TiN to MoOx. Thus, our simple and effective approach can facilitate HC collection under white light, thereby achieving high conversion efficiency for optoelectronic devices.
Keywords: Conductive atomic force microscopy; Electrostatic force microscopy; Energy harvesting device; Femtosecond transient absorption; High conversion efficiency; Hot carrier generation; Kelvin probe force microscopy; Metal oxide interface; Hot carrier; Local-probe force microscopy; Non-noble metal; Real-space photocurrent mapping